2007
DOI: 10.1089/jmf.2006.194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Soluble Fraction of Soybean on Lipid Profiles in Ovariectomized Rats Fed a Cholesterolemic Diet

Abstract: The increases in serum lipid profiles at the onset of menopause are regarded as a risk factor for cardiovascular disease. This study was designed to clarify the effects of a dried aqueous soybean extract and ovariectomy on lipid parameters in rats fed with cholesterolemic diet. Twenty-four 9-week-old female Sprague-Dawley rats were divided into two groups of 12 each and either sham-operated or ovariectomized. The ovariectomized and sham groups were then subdivided into groups of six and fed a semipurified case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Obesity easily leads to disorder of serum lipids (Durstine and Thomson 2001;Lee et al 2007). At present, the reports on the effects of exercise training on serum lipids disorder in OVX rats are not consistent.…”
Section: Discussionmentioning
confidence: 87%
“…Obesity easily leads to disorder of serum lipids (Durstine and Thomson 2001;Lee et al 2007). At present, the reports on the effects of exercise training on serum lipids disorder in OVX rats are not consistent.…”
Section: Discussionmentioning
confidence: 87%
“…Cholesterol changes in postmenopausal women [54] and in rodents after ovariectomy [55,56] are due to a lack of estrogen. Kamei et al [57] identified changes of gene expression in lipid metabolism including a decrease of SREBP1 in ovariectomized mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that supplementation with water-insoluble fish protein has a cholesterol lowering effect in ovariectomized rats (121). Another dietary protein source, that is soybean extract, has been found to modulate the level of serum TGs in ovariectomized rats fed a cholesterolemic diet (122). …”
Section: Impact Of Estrogen Deficiency On Body Weight and Physiologicmentioning
confidence: 99%